Parenting Gizi Berbasis Whatsapp: Literasi Digital Guna Mendukung Generasi Sehat Berprestasi - Reni Pawestuti Ambari Sumanto; Henny Puji Astuti; Ni Kadek Aris Rahmadani; R Agustinus Arum Eka Nugroho (Universitas Mathla'ul Anwar Banten, 2020)
NUTRITIONAL PARENTING ASSISTED WHATSAPP; DIGITAL LITERACY TO SUPPORT THE HEALTHY GENERATION OF ACHIEVERS. Parents have an important role in a family. Parental involvement in childcare has great potential to be developed. The potential of parents in parenting can be optimized through the potential of human and technological resources. In the current digital era, the potential for parental involvement can be strengthened by whatsapp-based digital literacy. Whatsapp is a technology resource that can convey various forms of messages such as text messages, voice messages, picture messages, even voice and video calls. This activity aims to empower parents in providing balanced nutrition for children through whatsapp-based parenting activities. The target group used as partners in this activity are parents of toddlers who attend Pos PAUD, at Pos PAUD Lestari II, Semarang City, Central Java. The method used in this activity was the initiation and parenting of whatsapp continuously. The results of activities carried out in the form of whatsapp-based nutrition parenting groups, the number of participants consisted of 20 parents, the results showed there were 85% of parents who had high enthusiasm when whatsapp parenting took place and 35% of parents were able to practice balanced diet for children. This activity needs to be continued given the limited number of parents who can practice balanced diet, the next activity can be in the form of literacy strengthening through peer education activities as an effort to increase parental involvement in fulfilling children's nutritional intake.